2011
DOI: 10.6001/ekologija.v57i4.2273
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of arsenic resistance prevalent in Bacillus species isolated from soil and ground water sources of India

Abstract: Arsenic is a naturally occurring element and its contamination of soil and groundwater is a major threat to the environment and human health. The ubiquity of arsenic in the environment has led to the evolution of the arsenic defence mechanism in certain microbes. The present study highlights identical mechanisms of arsenic resistance in two bacterial strains, namely AG24 and AGM13, which were taken from two different ecosources and states of India. The phylogenetic analysis of the strains using 16S rDNA sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The result of AAS analysis revealed that arsenic which entered the cell was emitted out of the cell due to the presence of active e ux mechanism of resistance in the isolate. Similar results were reported in a studySaluja et al 2011, in which the 2 strains (AG24 and AGM13) exhibited a similar pattern of e ux of metal from the cell. Altogether these ndings emphasized the presence of arsenic e ux system in the isolated strain.…”
supporting
confidence: 89%
“…The result of AAS analysis revealed that arsenic which entered the cell was emitted out of the cell due to the presence of active e ux mechanism of resistance in the isolate. Similar results were reported in a studySaluja et al 2011, in which the 2 strains (AG24 and AGM13) exhibited a similar pattern of e ux of metal from the cell. Altogether these ndings emphasized the presence of arsenic e ux system in the isolated strain.…”
supporting
confidence: 89%